A 5-stage active control method with online secondary path modelling using decorrelated control signal. (July 2020) - Pradhan, Somanath; Qiu, Xiaojun
Highlights: Online secondary path modelling in active control system is proposed using the control signal. A five-stage systematic method is proposed for practical active control operation. Adaptive decorrelation filters improve the convergence speed of the secondary path modelling. Maintain control when both the primary and the secondary path change. Outperforms existing algorithms. Abstract: Time-varying primary and secondary paths in active control systems degrade the noise control performance. In this paper, a practical method is proposed for active control systems with online secondary path modelling using the decorrelated control signal. The proposed method consists of 5 stages, i.e., primary path estimation, controller initialization, secondary path estimation, primary and secondary path changing detection, and active control operation, where the speed of the secondary path modelling is improved by incorporating decorrelation filters. The simulation results demonstrate the proposed method is capable of tracking the changes in both primary and secondary paths, remodelling the secondary path, and maintaining the noise reduction performance and stability of the system when both primary and secondary paths change.